Poor immunological recovery among severely immunosuppressed antiretroviral therapy-naïve Ugandans - Nanzigu S; Kiguba R; Kabanda J; Mukonzo JK; Waako P; Kityo C; Makumbi F (HIV/AIDS: Research and Palliative Care, 2013)
Sarah Nanzigu,1,2 Ronald Kiguba,1 Joseph Kabanda,3 Jackson K Mukonzo,1 Paul Waako,1 Cissy Kityo,4 Fred Makumbi31Department of Pharmacology and Therapeutics, Makerere University College of Health Sciences, Kampala, Uganda; 2Department of Laboratory Medicine, Karolinska Institute, Stockholm, Sweden; 3Institute of Public Health, Makerere University College of Health Sciences, Kampala, Uganda; 4Joint Clinic Research Centre, Kampala, UgandaIntroduction: CD4 T lymphocytes remain the surrogate measure for monitoring HIV progress in resource-limited settings. The absolute CD4 cell counts form the basis for antiretroviral therapy (ART) initiation and monitoring among HIV-infected adults. However, the rate of CD4 cell change differs among patients, and the factors responsible are inadequately documented.Objective: This study investigated the relationship between HIV severity and ART outcomes among ART-naïve Ugandans, with the primary outcome of complete immunological recovery among patients of different baseline CD4 counts.Methods: Patients' records at two HIV/ART sites – the Joint Clinic Research Centre (JCRC) in the Kampala region and Mbarara Hospital in Western Uganda – were reviewed. Records of 426 patients – 68.3% female and 63.2% from JCRC – who initiated ART between 2002 and 2007 were included. HIV severity was based on baseline CD4 cell counts, with low counts considered as severe immunosuppression, while attaining 418 CD4 cells/µL signified complete immunological recovery. Incidence rates of complete immunological recovery were calculated for, and compared between baseline CD4 cell categories: <50 with ≥50, <100 with ≥100, <200 with ≥200, and ≥200 with ≥250 cells/µL.Results: The incidence of complete immunological recovery was 158 during 791.9 person-years of observation, and patients with baseline CD4 ≥ 200 cells/µL reached the end point of immunological recovery 1.89 times faster than the patients with baseline CD4 < 200 cells/µL. CD4 cell change also differed by time, sex, and site, with a faster increase observed during the first year of treatment. CD4 cell increase was faster among females, and among patients from Mbarara.Conclusion: Initiating ART at an advanced HIV stage was the main reason for poor immunological recovery among Ugandans. Earlier ART initiation might lead to better immunological responses.Keywords: baseline CD4 cells, HIV severity, immunological recovery, ART outcome, ART